Evaluating the Performance of Health Supply Chains Using Network Data Envelopment Analysis Model under Uncertainty Conditions in Selected Tehran Hospitals - Darbani, Shoaleh; Nazarimanesh, Leila; Mohammadi, Emran (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: Objective: The objective of this research is to expand the models of Network Data Envelopment Analysis with approaches to uncertainty for evaluating the performance of supply chains. Method: The method used in this research is descriptive and, in terms of outcome, falls under applied research. From a strategic research perspective, it is descriptive and cross-sectional retrospective based on an analytical approach, conducted through fieldwork and a survey method in the research community. A census method was employed. Findings: In this study, Razi Hospital, with a score of 0.99, has the highest average efficiency in outpatient services, while Sina Hospital, with a score of 0.139, has the lowest level of average outpatient efficiency among multi-specialty hospitals. Additionally, Yas Hospital, with an average efficiency of 0.99 in inpatient sections, has the highest efficiency, whereas Razi Hospital with a score of 0.58 has the lowest efficiency. Bahrami Hospital among children’s hospitals is in a better condition. Conclusion: Based on the findings of the research, it was determined that the use of the fuzzy Network Data Envelopment Analysis model with variables such as the number of doctors, the number of healthcare workers, active beds, total inpatient days, the number of outpatient visits, and the number of inpatients, can compare the performance of selected decision-making units providing services in the studied medical centers from the perspective of inputs and outputs and across the entire health service supply chain. In the long term, it serves as a suitable tool for officials and policymakers of the selected centers for continuous performance evaluation of these services.